Functions and Mechanisms of SAC Phosphoinositide Phosphatases in Plants - Mao, Yanbo; Tan, Shutang (Frontiers in Plant Science, 2021)
Phosphatidylinositol (PtdIns) is one type of phospholipid comprising an inositol head group and two fatty acid chains covalently linked to the diacylglycerol group. In addition to their roles as compositions of cell membranes, phosphorylated PtdIns derivatives, termed phosphoinositides, execute a wide range of regulatory functions. PtdIns can be phosphorylated by various lipid kinases at 3-, 4- and/or 5- hydroxyls of the inositol ring, and the phosphorylated forms, including PtdIns3P, PtdIns4P, PtdIns5P, PtdIns(3,5)P2, PtdIns(4,5)P2, can be reversibly dephosphorylated by distinct lipid phosphatases. Amongst many other types, the SUPPRESSOR OF ACTIN (SAC) family of phosphoinositide phosphatases recently emerged as important regulators in multiple growth and developmental processes in plants. Here, we review recent advances on the biological functions, cellular activities, and molecular mechanisms of SAC domain-containing phosphoinositide phosphatases in plants. With a focus on those studies in the model plant Arabidopsis thaliana together with progresses in other plants, we highlight the important roles of subcellular localizations and substrate preferences of various SAC isoforms in their functions.